English versus Vickrey Auctions with Loss Averse Bidders - Jonas von Wangenheim (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Evidence suggests that people evaluate outcomes relative to expectations. I analyze this expectation-based loss aversion (Köszegi and Rabin (2006, 2009)) in the context of dynamic and static auctions, where the reference point is given by the (endogenous) equilibrium outcome. If agents update their reference point during the auction, the arrival of information crucially affects equilibrium behavior. Consequently, I show that even with independent private values the Vickrey auction yields strictly higher revenue than the English auction, violating the well known revenue equivalence. Thus, dynamic loss aversion offers a novel explanation for empirically observed differences between these auction formats.
Keywords: D03; D44; 330; vickrey auction; english auction; expectation-based loss aversion; revenue equivalence; dynamic loss aversion; personal equilibrium